2021
DOI: 10.1186/s12889-021-11038-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and its relation to health-related quality of life in 3–10-year-old children

Abstract: Background Considering the reports of increasing sleep problems in children, affecting health and well-being in young children and their families, we found it important to gain more knowledge about sleep and its correlation to health-related quality of life (HRQoL) in young, healthy children. The aims with this study were to describe sleep quality, sleep duration, and HRQoL in healthy 3–10-year-old children and to test associations between children’s sleep and HRQoL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Second, according to the time displacement hypothesis, screen viewing may displace the time that could otherwise have been used for intellectually demanding activities or health-enhancing physical activities [33][34][35]. Lack of such activities might consequently lead to impaired HRQOL and more behavioral problems in children [36][37][38][39]. Third, the social withdrawal hypothesis has suggested that excessive screen time could hinder children's social interaction with their peers and parents, which may subsequently jeopardize children's psychosocial well-being and prosocial behaviors [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Second, according to the time displacement hypothesis, screen viewing may displace the time that could otherwise have been used for intellectually demanding activities or health-enhancing physical activities [33][34][35]. Lack of such activities might consequently lead to impaired HRQOL and more behavioral problems in children [36][37][38][39]. Third, the social withdrawal hypothesis has suggested that excessive screen time could hinder children's social interaction with their peers and parents, which may subsequently jeopardize children's psychosocial well-being and prosocial behaviors [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…13 Evidence is emerging that HRQOL is also adversely affected in community samples of children with milder sleep health issues, such as parent-reported sleep problems 14,15 or sleep initiation or maintenance difficulties. 16 However, little research has determined whether HRQOL is a factor in sleep in otherwise healthy children. A 2016 systematic review 6 reported an inverse association between sleep duration and HRQOL in 3 studies but rated such evidence as very low quality.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, poor sleep quality will reduce daytime alertness, which, in turn, may decrease the attention effect and lead to impaired academic performance [ 35 ]. In addition, students at the last ranking will encounter greater learning pressure, which may affect the quality of sleep [ 1 , 2 , 3 , 4 ]. Screen time was positively correlated with the sleep quality score of primary school students, this may be due to the screen light stimulating the brain and inhibiting melatonin production, resulting in an increase in sleep latency [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is closely related to the healthy growth of adolescents and has extensive public health significance. The American Academy of Sleep Medicine proposes that school-age children need to ensure 9–12 h of sleep to maintain their physical and mental health [ 1 ] Good sleep quality is conducive to the healthy growth, study, and life of adolescents. However, many studies have reported that children have many sleep-related problems.…”
Section: Introductionmentioning
confidence: 99%